2020
DOI: 10.7759/cureus.10105
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Tranexamic Acid in Patients With Proximal Femoral Tumor Resection Prosthesis

Abstract: Aim: The aim of this study is to evaluate the risk of thromboembolic events and amount of postoperative blood loss and transfusion in patients who received preoperative tranexamic acid (TXA) administration in proximal femoral resection and endoprosthesis of proximal femur malignant lesion. Methods: In this study, the data of 46 patients who underwent extensive resection and proximal femoral tumor prosthesis for proximal femoral bone malignancies were retrospectively reviewed. Patients were divided into two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The same results were found in other studies. 60,61 For example, Atalay et al 60 cancer lesions of the proximal femur. Other studies investigated different modalities of TXA use.…”
Section: Orthopedic Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…The same results were found in other studies. 60,61 For example, Atalay et al 60 cancer lesions of the proximal femur. Other studies investigated different modalities of TXA use.…”
Section: Orthopedic Surgerymentioning
confidence: 99%
“…The same results were found in other studies. 60 , 61 For example, Atalay et al 60 demonstrated that preoperative TXA (15 mg/kg as a bolus) significantly reduced postoperative bleeding amount and transfusion needs in wide-margin tumor resection and prosthesis surgery for cancer lesions of the proximal femur. Other studies investigated different modalities of TXA use.…”
Section: Clinical Usage and Efficacy Of Tranexamic Acid In Oncologic ...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a study of 90 patients undergoing endoprosthetic reconstruction for pathologic fractures secondary to primary sarcoma and metastatic bone disease, Hasse et al identified decreased odds of blood transfusion among individuals who received TXA (TXA[+]: 21% lower frequency of transfusions, p = 0.04) compared to those who did not. Similarly, outcomes following TXA administration in a 46‐patient series by Atalay et al studying patients with proximal femoral tumor resection for femoral bone malignancies demonstrated a decreased risk of transfusion (rate of transfusion: TXA[+] 46% vs. TXA[−] 93.5%, p = 0.001) 13,14 . Alternatively, Owen et al found no significant difference in their study looking at transfusion rates in 66 individuals following bipolar hemiarthroplasty for impending or completed pathologic fracture of the femoral neck (TXA[+]: 36.4% vs. TXA[−]: 36.4%, p = 1.000) 15 .…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Currently, the literature regarding TXA utilization for neoplastic diseases of the lower extremity is limited to three studies. [13][14][15] As such, orthopedic oncologic surgeons may be hesitant to administer IV TXA before surgery for neoplastic pathologic fractures of the lower extremity due to the concern that the antifibrinolytic properties of TXA inhibiting clot dissolution may exacerbate the risk of VTE in these hypercoagulable individuals. 13,14,16,17 Thus far, this has yet to be proven.…”
mentioning
confidence: 99%